The Impact of AI on Adolescent Cognition and Mental Health: An International Literature Review (2024-2026) - KRUTI, Ida; KAZA, Arjana; SMITH, Klevisa (Journal of Ecohumanism, 2026)
The influence of artificial intelligence (AI) affects adolescents' academic performance, psychological development, and cognitive evolution. Artificial intelligence has a positive as well as a negative effect adolescents have found in many studies. This literature review focused on a collection of descriptive and empirical articles that were published between January 2024 and April 2026 in English language, examining how AI influences adolescents across three domains: academic performance, cognitive development, and psychological well-being. This literature review includes findings from 13 different countries including the United States, China, Japan, Argentina, Australia, Canada, Great Britain, Germany, Spain, Italy, Romania, Indonesia, and Albania. To identify relevant literature, searches were conducted using ResearchGate, Google Search, PubMed, Web of Science, and Google Scholar. The collected data indicate that the education outcomes, cognitive trajectories, and psychological health of adolescents are significantly influenced by their engagement with artificial intelligence. The review emphasizes the need for balanced use of AI in education and outlines essential directions for future research regarding the developmental impacts.